A High Throughput Assay to Identify Small Molecule Modulators of Prostatic Acid Phosphatase - Larsen, Rylan S (Bentham Open, 2009)
Prostatic acid phosphatase (PAP) is expressed in nociceptive neurons and functions as an ectonucleotidase. Injection of the secretory isoform of PAP has potent antinociceptive effects in mouse models of chronic pain. These data suggested that a small molecule activator of PAP may have utility as a novel therapeutic for chronic pain, while inhibitors could be used to acutely inhibit PAP in vitro and in vivo. To identify small molecule modulators of PAP activity, we validated a high throughput, fluorescence-based biochemical assay and then used this assay to screen a compound library. We decreased the frequency of false positive activators by subtracting compound fluorescence from the final assay fluorescence. This approach significantly reduced the number of false positive activators found in the screen. While no activators were confirmed, seven novel inhibitors of PAP were identified. Our results suggest this high throughput assay could be used to identify small molecule modulators of PAP activity.